The selection of interval boundaries of input and output data method for obtaining complete probabilistic characteristics; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Bay Yu. D. Yuly Dmitrievich; Shmoilov A. Anatoliy; Gusev A. S. Alexander Sergeevich; Razzhivin I. A. Igor Andreevich (2017, 2017)
Title screen